Tingkat Pendidikan dan Perilaku Kadarzi Ibu dengan Status Gizi Balita Usia 0-59 Bulan di Posyandu Rajawali Dusun Karangrejek Imogiri Bantul D.I Yogyakarta - Prasetiyorini, Azwandaru (Jurnal Riset Daerah, 2021)
In 2017 there were 17.8% of toddlers underweight and 29.6% experience stunting as well as several other nutrition related problems. This is caused by many factors such as the low level of mother's knowledge. The level of knowledge is one of them caused by the mother's education which is low, and the lack of mother's awareness of the application of Kadarzi in the family. Data from Health Office of Bantul shows the Lowest Kadarzi is in the working area of the Imogiri II Health Center as much as 857 or 95.22%. The aim of this this research is to find the correlation between the level of education and behavior of the mother's Kadarzi with the nutritional status of toddlers in Posyandu Rajawali, Imogiri, Bantul Regency, D.I.Yogyakarta, 2019. The type of this research is descriptive quantitative, with a cross-sectional approach. Total population of 33 toddlers, with total sampling technique which means that the entire population in the study was taken. The isntrument of this research is questionnaire with data analysis using univariate test analysis and bivariate test (Chi Square and Kendall Tau). The results of the Kendall Tau Test analysis (sig 0.216), which means there is no significant correlation between the level of education of mothers with the nutritional status of children under five. While with the chi square test there is a significant correlation between mother’s behavior about Kadarzi with the nutritional status of children under five in the Posyandu Rajawali, Posyandu Rajawali Karangrejek Village working area Puskesmas Imogiri II Bantul Regency. The result shows that the value of Chi Square (x2) is 25,592, sig 0,000. This shows that the value of p <0.05. There is no significant correlation between mother's education level and the nutritional status of toddlers. There is a significant relationship between mother's behavior about Kadarzi with the nutritional status of toddlers in Posyandu Rajawali, Karangrejek, working area of Imogiri II Health Center, Bantul Regency.